Sedation in mechanically ventilated patients—time to stay awake? - Moreira, Fabio Tanzillo; Neto, Ary Serpa (Annals of Translational Medicine, 2016)
On June, 2016, Klompas and colleagues published an article in the Chest entitled “Associations between different sedatives and ventilator-associated events, length of stay, and mortality in patients who were mechanically ventilated”, which investigated the effects of different sedatives on ventilator-associated events (VAEs), length of stay, and mortality in patients who were mechanically ventilated. This study used data of over 9,603 patients in order to investigate patients over the age of 18 who underwent mechanical ventilation for more than 3 days over a 7-year period in a large academic medical center. The investigators found that propofol and dexmedetomidine were associated with less time to extubation compared with benzodiazepines, but dexmedetomidine was also associated with less time to extubation vs propofol. This study raises important questions about the sedation of critically ill patients.